Принцип трансдисціплінарності, історичний метод та проблема часу з позиції філософського аналізу сучасної екології - Годзь, Наталія Борисівна (Національний університет "Острозька академія", 2014)
У статті досліджується предмет екології та екологічної футурології, розглядаючи питання принципу трандисціплінарності. Аналізуються стратегії збереження довкілля та взаємозв’язок поміж екологією, економікою та новітніми технологіями. Досліджується питання розуміння культури й зв'язку екології та екологічних досліджень з питаннями розвитку науки.

Given article we continue the analysis of the subject «futurology».We examine variable principles methods’ coming from position of analysis of modern ecology. We one of the exceptional characteristic features of humankind is the ability to critically evaluate the current situation on the one hand, and on the other hand to likewise enthusiastically create and live in the world of illusions. So we are trying to exist in this in this world fighting and at the same time creating presumable field for conflicts and ecological, technologic problems. Today, we have new conflict situations and conflict development of mankind makes us change. It should be mentioned that at certain times there was a key problem connected with «compulsory knowledge» for an «educated person» and «the younger generation». Link of times and processes in scientific word view is lost due to going into details and refinements of biological education system. One can see negligence to the authors who were the at the source of natural science, namely to those who formed our modern biological worldview. Today, if we have a close look at the process of scientific worldview development, the fullness of scientific worldview we will be able to find the starting point of our development problems, including the problems that are related to ecological problems, when the admiration at mechanical defeated common wisdom. Proceeded our investigation scientific work, we continue defending several statements. The first one is based upon the accentuation of a strict system which accepts as valid ones different definitions of Ecology. These definitions are multidirectional proceeding from the time of their origin, and consequently they are defined through the sphere they serve. But Ecology in the global sense cannot be restricted to environmental protection technologies. It is not the main purpose of Ecology to fight for «purity of environment». On the whole the interests of Ecology lie in the parameters of growth, limits of existence. It can be said that Ecology is a science about the system as it is. But adding new meanings and contents plays not only appositive role, but also a negative one, creating a field of conflicts which can be based on different understanding of the subject and object of Ecology which can cause demagogy and over simplicity. We insist on philosophical comprehension of ecology, developing «The Philosophy of Ecology», «The Ecology Futurology».
The principle of trans disciplinary, historical method and problem of the time in position philosophical analysis the modern ecology
Keywords: довкілля; технології природозберігаючі; світогляд; футурологія екологічна; surroundings; nature protection technologies; weltanschauung; ecological futurology